Conserved and specialized functions of Type VII secretion systems in non-tuberculous mycobacteria. Issue 7 (5th July 2021) - Lagune, Marion; Petit, Cecile; Sotomayor, Flor Vásquez; Johansen, Matt D.; Beckham, Kathrine S. H.; Ritter, Christina; Girard-Misguich, Fabienne; Wilmanns, Matthias; Kremer, Laurent; Maurer, Florian P.; Herrmann, Jean-Louis
Abstract : Non-tuberculous mycobacteria (NTM) are a large group of micro-organisms comprising more than 200 individual species. Most NTM are saprophytic organisms and are found mainly in terrestrial and aquatic environments. In recent years, NTM have been increasingly associated with infections in both immunocompetent and immunocompromised individuals, prompting significant efforts to understand the diverse pathogenic and signalling traits of these emerging pathogens. Since the discovery of Type VII secretion systems (T7SS), there have been significant developments regarding the role of these complex systems in mycobacteria. These specialised systems, also known as Early Antigenic Secretion (ESX) systems, are employed to secrete proteins across the inner membrane. They also play an essential role in virulence, nutrient uptake and conjugation. Our understanding of T7SS in mycobacteria has significantly benefited over the last few years, from the resolution of ESX-3 structure in Mycobacterium smegmatis, to ESX-5 structures in Mycobacterium xenopi and Mycobacterium tuberculosis . In addition, ESX-4, considered until recently as a non-functional system in both pathogenic and non-pathogenic mycobacteria, has been proposed to play an important role in the virulence of Mycobacterium abscessus ; an increasingly recognized opportunistic NTM causing severe lung diseases. These major findings have led to important new insights into the functional mechanisms of these biological systems, their implication in virulence, nutrient acquisitions and cell wall shaping, and will be discussed in this review.